EXPRESSION OF REPORTER GENES IN TRANSFORMED INDICA RICE THROUGH Agrobacterium MEDIATED METHOD (Bangladesh Journal of Plant Breeding and Genetics, 2007)
Genetic transformation of rice (Oryza sativa L.) mediated by Agrobacterium tumefaciens has been confirmed for japonica varieties and extended to include more recalcitrant indica varieties. Scutellum-derived calli from mature seeds of Kasalath and BR-5 were used. The Agrobacterium tumefaciens strain, EHA101, harboring the binary vector pIG121Hm/Km/GUS was used for transformation. The vector contains b-glucuronidase (GUS) gene as a reporter gene and hygromycin resistance (HPT) as well as kanamycin resistance gene (NPTII) as selection genes in the T-DNA region. After co-cultivation with the bacteria, calli were inoculated on selection medium in which hygromycin concentration was 50 mg/l for Kasalath and 20 mg/l for BR-5. Carbenicillin (500 mg/l) was used for removal of Agrobacterium after co-cultivation. Inclusion of acetosyringone 50100 mM in the Agrobacterium suspension in co-culture medium increased the frequency of transformation. Frequency of transformed calli (hygromycin resistant cells) was 82% in Kasalath and 6% in BR-5. Regeneration efficiency from transformed calli in Kasalath was about 63% and in BR-5 was about 34%. Most of the transgenic plants were morphologically normal but seed fertility was lower than the control. In transformed calli, roots and immature inflorescence showed positive response in GUS assay. Presence of GUS, HPT and NPTII genes was confirmed by PCR analysis and PCR Southern blot analysis. Expression of GUS gene was 100% in T1 progeny of Kasalath, whereas that of HPT gene was 51%. BR-5 could not be tested because of low seed fertility of T0 plants. In T1 plants, seed fertility of transformed Kasalath was 79% which is lower than that of the respective non-transformants.DOI: http://dx.doi.org/10.3329/bjpbg.v20i1.10633